Asexual propagation of two sea anemone taxa for Banggai cardinalfish microhabitat enhancement. Issue 1 (March 2020) - Moore, A M; Yasir, I; A-Rappe, R; Ndobe, S; Jompa, J
Abstract: The iconic symbiosis with clownfish is not the only sea anemone-fish association. Several tropical sea anemones provide microhabitat for the Endangered (IUCN Red List) Banggai cardinalfish Pterapogon kauderni. Microhabitat loss from declining sea anemone populations is a serious threat to native P. kauderni populations or evolutionarily significant units (ESUs). One measure advocated to maintain and rehabilitate these P. kauderni ESUs is to restore microhabitat abundance. The objective of this study was to evaluate the feasibility of the asexual propagation of wild anemone broodstock with the subsequent release. Two species with which P. kauderni commonly associates ( Heteractis crispa and Entacmaea quadricolor ) were identified through field surveys. Parent anemones were bisected, cutting through the center of the oral disc. Propagules (half anemones) were placed in empty clam shells as hard substrate. Treatments provided different levels of protection from potential predators, in aquaria ( P. kauderni present/absent), concrete tanks ( P. kauderni and Diadema urchins excluded/not excluded) or in a net cage on the natural substrate (fish and invertebrate fauna including P. kauderni and Diadema setosum ). The cut edges of sectioned anemones joined together within seconds, with wounds typically healing in around 7 days and joins hard to see after 3-4 weeks. Growth was faster and long-term survival higher in the net cage compared to tanks for uncovered and covered anemones. The results indicate the potential for this propagation method in the context of P. kauderni conservation and suggest sectioned anemones should be moved to the natural rehabilitation areas once capable of adhering firmly to a hard substrate.